2017
DOI: 10.19171/uefad.369242
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing of the Relationships between Organizational Justice and Organizational Trust of Teachers

Abstract: ÖZET (2007) tarafından geçerlik ve güvenirlik çalışmaları tekrar yapılan "Okullarda Örgütsel Güven Ölçeği" kullanılmıştır. Yapılan analizler sonucunda örgütsel adaletin örgütsel güveni anlamlı düzeyde yordadığı sonucuna ulaşılmıştır. Ayrıca öğretmenlerin örgütsel adalet düzeylerinin yüksek, örgütsel güven düzeylerinin ise orta düzeyde olduğu tespit edilmiştir.Anahtar Sözcükler: Öğretmen, örgütsel adalet, örgütsel güven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In addition, it was concluded that organizational justice had a strong effect on organizational trust. This result coincides with previously conducted research results (Polat & Celep, 2008;Kulekci Akyavuz, 2017;Ozgan, 2011;Yildiz, 2013). Based on this result, it can be said that organizational trust perceptions will increase as educational stakeholders' perception of justice increases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it was concluded that organizational justice had a strong effect on organizational trust. This result coincides with previously conducted research results (Polat & Celep, 2008;Kulekci Akyavuz, 2017;Ozgan, 2011;Yildiz, 2013). Based on this result, it can be said that organizational trust perceptions will increase as educational stakeholders' perception of justice increases.…”
Section: Discussionsupporting
confidence: 93%
“…When the research conducted is examined, it is seen that the organizational trust has a positive relationship with organizational justice (Polat & Celep, 2008;Kulekci Akyavuz, 2017;Ozgan, 2011;Yildiz, 2013), organizational commitment (Yilmaz, 2008;Ozgan, 2011;Aybar & Marsap, 2018;Altunay, 2017), organizational support (Polat, 2010;Yiimaz & Turan, 2015;Uzun, 2018;Ergun, 2017), organizational citizenship (Karadal & Erdem, 2018;Polat & Celep, 2008;Uzun, 2018;Dede, 2017), job satisfaction (Bil, 2018;Celik, 2015;Horuz;Yalcin, 2014) and ethical leadership (Cemaloglu & Kilinc, 2012;Kuru, 2017;Pasa & Nergis Isik, 2017). On the other hand, it can be seen that organizational trust has a negative relationship with organizational silence (Pasa & Nergis Isik, 2017;Cakinberk, Dede & Yilmaz, 2014;Saglam, 2016), organizational cynicism (Akin, 2015;Akyuz, Kesen & Ograk, 2016;Kahveci, 2015), burnout (Caglar, 2011;Turhan & Erol, 2017;Yilmaz, 2014) and mobbing (Egerci, 2009;Demirdag, 2017;Cemaloglu & Kilinc, 2012).…”
Section: Introductionmentioning
confidence: 99%